2007
DOI: 10.1039/b708583d
|View full text |Cite
|
Sign up to set email alerts
|

Multi-layered analyses using directed partitioning to identify and discriminate between biogenic amines

Abstract: Multiple layers of statistical analyses were used to decipher the response from a single, cross-reactive conjugated polymer (1) providing enhanced classification accuracies over traditional multivariate statistical approaches. This analysis was demonstrated by classifying a series of seven biologically relevant, nonvolatile amines (i.e. biogenic amines). If only a single layer of analysis was employed (linear discriminant analysis), 89% classification accuracy was achieved lacking any concentration information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…The detection limit of BDA was estimated to be at the parts per billion (ppb) level, which is noticeably more sensitive than previously reported colorimetric sensors. [14] The dramatic enhancement in the fluorescence intensity upon addition of BDA is rationalized in terms of aggregation triggered by divalent interactions of BDA with 1 appending carboxylic acid groups, as illustrated in Scheme 1c. Indeed, after filtration with an 0.45 mm pore size membrane, the solution returned to being nonluminescent.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The detection limit of BDA was estimated to be at the parts per billion (ppb) level, which is noticeably more sensitive than previously reported colorimetric sensors. [14] The dramatic enhancement in the fluorescence intensity upon addition of BDA is rationalized in terms of aggregation triggered by divalent interactions of BDA with 1 appending carboxylic acid groups, as illustrated in Scheme 1c. Indeed, after filtration with an 0.45 mm pore size membrane, the solution returned to being nonluminescent.…”
Section: Resultsmentioning
confidence: 98%
“…Alternatively, Lavigne et al recently demonstrated a colorimetric method for the detection and identification of amines by using carboxylic acid functionalized poly(thiophene). [14] The chromic responses resulting from the nonspecific interaction between the polymer and amines were utilized to distinguish amines by using statistical analysis. A sensor array based on analyte-specific patterns arising from the differential binding affinity of a set of nonspecific receptors is attractive, because this sensing approach simplifies the sensor design.…”
Section: Introductionmentioning
confidence: 99%
“…This technique was further applied to detect biogenic amines related to food freshness, even in complicated fish matrices (Fig. 14.10) [126,127]. As can be seen in the figure, this polythiophene sensor had a linear response to varying concentrations of histamine.…”
Section: Conjugated Polymersmentioning
confidence: 93%
“…The Lavigne group has used conjugated polymer aggregation in colorimetric sensory systems for the detection of structurally similar diamines [86], biogenic amines [126,127], and soft divalent metal ions [128]. Carboxylatefunctionalized polythiophenes (14) were used in this work, which would form favorable connections with the analytes listed through both electrostatic and hydrogen-bonding interactions.…”
Section: Conjugated Polymersmentioning
confidence: 99%
“…In other words, the origin of BAs can be categorized as endogenous or exogenous. [1][2][3] In the human body BAs are formed by various metabolic process and are necessary in diverse physiological functions. For example, spermine and spermidine regulate growth, serotonin acts as a neural transmitter, histamine and tyramine are inflammation agents, and BAs are involved in cell-membrane equilibrium, cell propagation, and the synthesis of RNA, DNA, and various proteins.…”
Section: Introductionmentioning
confidence: 99%